Musculoskeletal problems and its influencing factors among automobile factory workers, 1999 - Nur Aiza Zakaria,; KG Rampal, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A study on musculoskeletal problems was conducted among automobil factory workers in Pahang from June1999 until September 1999. The objective of this study is to determine the prevalence of musculoskeletal problems among the workers and the factors involved. The study design was a crosssectional study where 356 workers were taken as samples from the production section. This study showed the prevalence of backache was the highest (74.2%), followed by cervicobrachial problems (67 .10;0 ), upper limb problems (61.0%) and knee joint problems(36.6%). Chi square and t tests showed there were associations found between harmful biomechanical problems e.g. awkward postures, lifting and carrying; vibration at workplace; repetitive movements; uncomfortable workplace; lack of rest and experience and psychological factors with musculoskeletal problems. In conclusion, musculoskeletal problem is a major problem in this industry which needs to be controlled.